2023
DOI: 10.1186/s12884-023-05360-8
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of intravenous remifentanil on umbilical artery serum-derived exosomes in parturients undergoing epidural anesthesia: a randomized trial

Abstract: Background Umbilical artery serum-derived exosomes (UEs) serve as messengers for maternal–fetal information exchange and cellular regulation. Intravenous remifentanil could be considered as an effective adjunct to epidural anesthesia in providing a favorable analgesia effect for cesarean section (C-section), but its effects on UEs are currently unknown. Methods From 01/12/2021 to 30/06/2022, eligible parturients scheduled for repeated C-section at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Exosomes, minute extracellular vesicles, play a pivotal role in cellular communication, serving as dynamic messengers that convey bioactive molecules between cells. 19 The biogenesis of exosomes is intricately linked to the endosomal pathway, a cellular process that begins with endocytosis within early endosomes. 20 During this phase, the cell engulfs membrane proteins and extracellular materials, setting the foundation for the formation of intraluminal vesicles (ILVs).…”
Section: Exosomes: Biology and Therapeutic Potentialmentioning
confidence: 99%
“…Exosomes, minute extracellular vesicles, play a pivotal role in cellular communication, serving as dynamic messengers that convey bioactive molecules between cells. 19 The biogenesis of exosomes is intricately linked to the endosomal pathway, a cellular process that begins with endocytosis within early endosomes. 20 During this phase, the cell engulfs membrane proteins and extracellular materials, setting the foundation for the formation of intraluminal vesicles (ILVs).…”
Section: Exosomes: Biology and Therapeutic Potentialmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the author reported that in the article the title "trial" was incorrectly written as "trail". In addition, Dr. Xiangqing Xiong's affiliation is only “the First Affiliated Hospital of Wenzhou Medical University” and is presented correctly in this correction article.…”
mentioning
confidence: 99%